INTERRELATED OPTION FOR THE POOR AND THE EARTH - D.J. Margaret (Asian Horizons, 2015)
The global world which is characterized by postmodern world view is beset not only with numerous basic socio-economic, religio-cultural problems but also with ecological problems. If humans continue to oppress the poor and to destroy the ecosystems, then we will soon run out of balance of our life on this universe. The earth is ultimately a common heritage, the fruits of which are for the benefit of all. An Integral ecological care of the earth invites the human community to view it as God-centred and be accountable. The option for the poor and the earth are interrelated. Nature will truly enjoy its second spring only when humanity has compassion for its own members. A right education in ecological care and genuine concern for the poor entails a transformation in ways of thought, behaviour, and lifestyle. Everyone must recognize her/his obligation to contribute to the restoration of a healthy environment and humanity.